Analisis kinerja tenaga pendidik di RA Miftahul Huda Karangploso - Nurdin, Zilyanadelia Wahyu Veronellita (Maliki Interdisciplinary Journal, 2024)
This study aims to determine the performance analysis of teaching staff at RA Miftahul Huda Karangploso. The method used in this research is to use a qualitative approach with literature review and observation results. The discussion and theories obtained are based on the results of analysis from articles and journals as well as direct observation at school. Based on this research, it can be concluded that the analysis of the performance of teaching staff at RA Miftahul Huda Karangploso is in accordance with the theory from the literature review that has been obtained.